Pengaruh Pelatihan, Iklim Kerja, dan Rotasi Kerja terhadap Kinerja Pegawai Perusahaan Daerah Air Minum (PDAM) Tirta Perwira Purbalingga - Kamila Faran Primastiti; Hima Barima; Heni Purwatini (Jurnal Bisnis Kreatif dan Inovatif, 2025)
The Regional Drinking Water Company (PDAM) Tirta Perwira Purbalingga is a regional institution that provides clean water services to 62,748 customers in Purbalingga Regency. The company’s performance is strongly influenced by the quality of its human resources. This study aims to analyze the effect of training, work climate, and job rotation on employee performance. The research used a quantitative approach with descriptive methods and data processing through SPSS version 25.0. The population consisted of 164 employees, with a sample of 62 respondents determined by the Slovin formula (10%) using stratified random sampling. The results showed that training and work climate had a positive and significant effect on employee performance, while job rotation did not have a significant effect. The coefficient of determination (R²) was 96.4%, meaning that the three variables together explained 96.4% of employee performance, while the remaining 3.6% was influenced by other factors not examined in this study. These findings indicate that systematic training and a supportive work climate are the dominant factors in improving performance, whereas job rotation requires better alignment with employee competencies to be effective. In conclusion, PDAM Tirta Perwira needs to strengthen its training programs, foster a conducive work atmosphere, and carefully evaluate job rotation policies. The results of this study are expected to contribute to the development of human resource management strategies and provide reference material for future research on organizational performance.